Tuition-free Students’ Profiling during Covid-19 in Kidapawan City, Philippines - Ramos, Sarah (Technium: Romanian Journal of Applied Sciences and Technology, 2021)
Learning effectiveness using relevant modalities to students is necessary. Many tuition-free institutions were experiencing cons amidst the transition of new normal education due to the COVID-19 pandemic. The present study sought to identify the learning delivery modality that the students wanted to utilise amidst the COVID-19 encounter. Specifically, it aimed to determine the profile of the tuition-free students; determine the common academic problems experienced by the respondents; and recognise the modality of contemporary instruction to address the problem. The gathering of data happened twice to clarify the specific responses of the respondents. The frequency count and percentage were extracted to determine the result. The result of the study revealed that the majority of the student-respondents were from Kidapawan City utilising Mobile Data and Cellphone during classes. Due to the students’ lack of means for learning, they were experiencing Slow Connectivity. It was concluded that the tuition-free students were unprepared to have blended learning which they preferred Modular for contemporary instruction. Due to the prevention of spreading COVID-19, it was then recommended to better prepare blended modalities particularly online learning since it became accessible and feasible for the said institution to execute despite the abrupt transition to secure continuous education.